2013
DOI: 10.1136/jmedgenet-2012-101485
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of corpus callosum and optic nerve hypoplasia due to mutations inSLC25A1encoding the mitochondrial citrate transporter

Abstract: We report for the first time a patient with a mitochondrial citrate carrier deficiency. Our data support a role for citric acid cycle defects in agenesis of corpus callosum as already reported in patients with aconitase or fumarate hydratase deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 34 publications
6
71
0
Order By: Relevance
“…This is the fifth report of DL-2HGA, our proband being the twentieth affected individual reported to date (Nota et al 2013;Chaouch et al 2014;Prasun et al 2015;Edvardson et al 2013). As far as we are aware, no other patient with DL-2HGA has been described to have a specific respiratory chain defect (complex IV deficiency) on muscle biopsy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is the fifth report of DL-2HGA, our proband being the twentieth affected individual reported to date (Nota et al 2013;Chaouch et al 2014;Prasun et al 2015;Edvardson et al 2013). As far as we are aware, no other patient with DL-2HGA has been described to have a specific respiratory chain defect (complex IV deficiency) on muscle biopsy.…”
Section: Discussionmentioning
confidence: 87%
“…The major described function of the CIC is to shuttle mitochondrially synthesized citrate to the cytoplasm, where it (1) furnishes (via citrate lyase) acetyl-coA to support fatty acid and sterol synthesis and (2) exerts feedback control over glycolysis by allosterically inhibiting phosphofructokinase. Recently, recessive mutations of SLC25A1 in 20 persons with combined D,L-2-hydroxyglutaric aciduria (DL-2HGA; OMIM #615182), a disorder characterized clinically by severe developmental delay, hypotonia, and seizures, have been described (Edvardson et al 2013;Nota et al 2013). With subsequent reports, the clinical phenotype of DL-2HGA has since been expanded to include secondary microcephaly, hypoplasia or agenesis of the corpus callosum, optic nerve hypoplasia, dysmorphic features, lactic acidosis, and recurrent apneic crises (Chaouch et al 2014;M€ uhlhausen et al 2014;Prasun et al 2015).…”
Section: àmentioning
confidence: 99%
“…The first is based on the inhibition of mitochondrial CIC activity by the specific substrate analogue 1,2,3-benzene-tricarboxylate (BTA) Infantino et al, 2011a;Cappello et al, 2012;Catalina-Rodriguez et al, 2012) and the second by siRNA gene silencing Morciano et al, 2009;Infantino et al, 2011a;Catalina-Rodriguez et al, 2012). Recently, by mutational analysis of the SLC25A1 gene (Edvardson et al, 2013;Nota et al, 2013), different mutations were identified in patients with agenesis of corpus callosum and hydroxyglutaric aciduria. Furthermore, direct measurements by liquid chromatography-tandem mass spectrometry (van de Wier et al, 2013) and nuclear magnetic resonance-based methods (Hricak, 2005;Kline et al, 2006) highlighted altered citrate levels in non-alcoholic fatty liver disease (NAFLD) and prostate cancer, respectively.…”
Section: The Multifunctional Role Of Citratementioning
confidence: 99%
“…Recently, agenesis of the corpus callosum, a birth defect that occurs in different human congenital syndromes, and optic nerve hypoplasia have been associated with mutations in the SLC25A1 gene (MIM 190315) (Edvardson et al, 2013). Two mutations (G130D and R282H), located in highly conserved positions of CIC through evolution, significantly affect protein function, as demonstrated by experiments performed with a yeast strain harboring human CIC mutations at equivalent positions in the orthologous yeast protein, which exhibits a growth defect under stress condition and a marked loss of citrate transport activity in reconstituted liposomes (Edvardson et al, 2013). As consequence of loss or marked reduction of CIC activity, citrate/ isocitrate cytosolic level, TCA cycle flux, and NADPH content decreased, but oxidative stress and ROS toxicity increased.…”
Section: Citrate In Neurodevelopmental Syndromes and Hydroxyglutaric mentioning
confidence: 99%
“…Indeed, inhibition of citrate pathway leads to a significant reduction of ROS as well as lipid peroxidation levels, common landmarks of subjects with DS (Brooksbank and Balazs 1984), suggesting that mechanisms other than imbalance in the SOD1/ catalase (Feaster et al, 1977) are also involved in the prooxidant status in the DS. (Edvardson et al, 2013;Nota et al, 2013;Chaouch et al, 2014) cause a rare inherited metabolic disorder, combined 2-hydroxyglutaric aciduria (2-HGA), characterised by epileptic encephalopathy, respiratory insufficiency, developmental arrest and early death. The origin of elevated 2-HG due to SLC25A1 deficiency is still unclear, but has been attributed to accumulation of citrate and other tricarboxylic acid (TCA) cycle intermediates in the mitochondria including α-ketoglutarate, which in turn is converted to 2-HG (Kranendijk et al, 2012) (see section The oxoglutarate carrier OGC).…”
Section: The Citrate Carrier Cic (Slc25a1)mentioning
confidence: 99%